Rancang Bangun Mesin Pencetak Terasi Untuk Memudahkan Proses Penjualan Dengan Berat 110 Dan 250 Gram - Robert Napitupulu; Zaldy Kurniawan; Erin Aftarini; Firdi Irawan; Gilang Perdana (Manutech : Jurnal Teknologi Manufaktur, 2016)
Terasi is one of the basic ingredients in the food processing, particularly in the area of the base Kep.Bangka Belitung province. The paste of the terasi in the market are generally shaped in the massive beams that make them difficult to distribute to the sellers because the market demand such varied size of 110 and 250 grams. The purpose of this study is to design and make the terasi paste printing machine which can cut to size shrimp paste with a uniform weight of 110 and 250 grams. The method used in solving this problem is based on the method design: Identification of Problems, collecting data by observation, interview, and literature, and performing data processing, Creating the design, manufacture machinery / fabricating, assembling and final testing and analyzing. The test result is that the form of paste printed measuring 61x30x45 with an average weight of 110 grams and the paste to paste the printed results of measuring 150x30x45 with an average weight of 250 grams shrimp paste.